Evaluation of patients admitted with musculoskeletal tuberculosis: sixteen years’ experience from a single center in Turkey - Mikail Ozdemir; H. Gulnihal Ozdemir (BMC Musculoskeletal Disorders, 2021)
Abstract Background The aim of our study was to describe musculoskeletal system tuberculosis (TB) as a single-center experience. Methods This is a retrospective observational study conducted at a TB Dispensary in the east Mediterranean part of Turkey between 2004 and 2020. The clinical and demographic characteristics including age, gender, involvement location and duration of illness, presenting complaint, local examination findings, treatment outcome were retrieved and analyzed from the case files. Statistical analyses were performed using SPSS Statistics version 17.0 (IBM). The normality of data analysed by using Kolmogorov-Smirnov. The descriptive statistics were reported as mean ± standard deviation, medians, and ranges (min-max). Results Overall, 31 patients (3.2 % of all TB cases) with a mean age of 44.2 ± 16.7 years had musculoskeletal tuberculosis. The mean duration of treatment was 12.9 ± 5.5 months. Of the 31 patients, six (19.4 %) had concomitant pulmonary TB. One of the patients was in the pediatrics age group, and two of them were in the geriatric group. The most affected area was the vertebra. The most common complaint of the patients was back pain and seen in 22 patients (70.9 %). Conclusions The physicians should be suspicious about the diagnosis of musculoskeletal TB disease. If the diagnosis and treatment are delayed, spinal damage and other consequences might be incurable.